2014
DOI: 10.1007/s10661-014-3986-0
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of large linear pipeline construction on soil and vegetation in ecologically fragile regions

Abstract: Long-distance pipeline construction results in marked human disturbance of the regional ecosystem and brings into question the safety of pipeline construction with respect to the environment. Thus, the direct environmental impact and proper handling of such large projects have received much attention. The potential environmental effects, however, have not been fully addressed, particularly for large linear pipeline projects, and the threshold of such effects is unclear. In this study, two typical eco-fragile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 48 publications
0
6
0
2
Order By: Relevance
“…Xiao et al. (2014), Low (2016), and Xiao et al. (2017) found similar results, with invasive species thriving in disturbed areas, reducing plant diversity and resulting in difficulty of native species reestablishment after pipeline installation.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Xiao et al. (2014), Low (2016), and Xiao et al. (2017) found similar results, with invasive species thriving in disturbed areas, reducing plant diversity and resulting in difficulty of native species reestablishment after pipeline installation.…”
Section: Resultsmentioning
confidence: 74%
“…Desserud et al (2010) found that invasive species like Kentucky bluegrass (Poa pratensis L.) dominated many of the native grass species in disturbed areas, while undisturbed sections had higher percentage cover by native fescue grass species. Xiao et al (2014), Low (2016), andXiao et al (2017) found similar results, with invasive species thriving in disturbed areas, reducing plant diversity and resulting in difficulty of native species reestablishment after pipeline installation. Olson and Doherty (2012) found that, in naturally diverse wetland areas in Wisconsin, pipeline installation in these areas resulted in lower species richness and higher dominance of invasive species when compared with undisturbed wetland areas.…”
Section: Crop Yield and Plant Productivity Responsesmentioning
confidence: 74%
“…5). The weight of each index was determined by using entropy method, which is a quantitative and objective method in assigning weight (Xiao, Wang, Shi, Yang, & Chen, 2014).…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…In this field, the downflow was obstructed by a driveway and, therefore, the field itself remained uncultivated and abandoned for many years, as the faulty drainage impeded a normal crop growth and production. Water stagnation could be avoided by placing a pipe below the driveway to remove the water to a depth sufficient for guaranteeing a soil explorable by plant roots for at least 1 m [50]. The flooded water reached a small field having a low slope and a short downflow line.…”
Section: Hydraulic-infrastructural Riskmentioning
confidence: 99%